2016
DOI: 10.1097/ijg.0000000000000489
|View full text |Cite
|
Sign up to set email alerts
|

Combined Approach to Phacoemulsification and Trabeculectomy Results in Less Ideal Refractive Outcomes Compared With the Sequential Approach

Abstract: Purpose: To compare the refractive outcomes of combined versus sequential trabeculectomy and then phacoemulsification. Methods: We compared eyes that underwent uncomplicated combined phacotrabeculectomy (combined group, 87 eyes), phacoemulsification at least 3 months after trabeculectomy (sequential group, 56 eyes), and phacoemulsification only (control group, 78 eyes) between January 1, 2006 and January 1, 2014. The main outcome measure was refractive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 14 publications
3
16
0
1
Order By: Relevance
“…It means that phacotrabeculectomy was effective not only for IOP control but also for stable refractive outcomes. Previous studies reported that myopic shift occurs after phacotrabeculectomy compared to phacoemulsi cation alone [11,[23][24][25]. A decreased ACD after trabeculectomy causes a myopic shift, and a decreased AL after trabeculectomy causes a hyperopic shift, conversely.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It means that phacotrabeculectomy was effective not only for IOP control but also for stable refractive outcomes. Previous studies reported that myopic shift occurs after phacotrabeculectomy compared to phacoemulsi cation alone [11,[23][24][25]. A decreased ACD after trabeculectomy causes a myopic shift, and a decreased AL after trabeculectomy causes a hyperopic shift, conversely.…”
Section: Discussionmentioning
confidence: 97%
“…Most of the studies that focused the refractive outcomes of phacotrabeculectomy analyzed only shortterm refractive outcomes less than 6 months [11,18,[22][23][24][25], and one study reported by Chung et al [12] had a limitation that the follow-up period of the control group was average of 4.81 months. Therefore, the present study is clinically signi cant because we analyzed long-term refractive outcomes of phacotrabeculectomy up to 24 months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So erreichten hier knapp 46,2 % der Augen mindestens 3 Monate nach dem Eingriff ein postoperatives sphärisches Äquivalent im Bereich von ±0,5 dpt. im Vergleich zu lediglich 27,6 % bei den kombinierten Eingriffen [15].…”
Section: Studienergebnisseunclassified
“…One study compared the eyes that underwent phacoemulsification at least 3 months after trabeculectomy with the eyes that did not undergo glaucoma surgery and reported that the change in IOP is negatively correlated with refractive surprise; a correlation between lower postoperative IOP or greater IOP reduction and the amount of axial length reduction was expected [14]. In addition, a recent study has revealed that refractive outcome is inferior in combined versus subsequent trabeculectomy [15]. On the other hand, a study comparing combined trabectome-cataract surgery with cataract-alone surgery did not find any differences in refractive and visual outcomes and a retrospective analysis showed favourable refractive outcomes in patients undergoing simultaneous cataract extraction with trabeculectomy or glaucoma drainage device surgery [16, 17].…”
Section: Introductionmentioning
confidence: 99%